Factors associated with deep tissue injury in male wheelchair basketball players of a Japanese national team - Hirotaka Mutsuzaki; Kaori Tachibana; Yukiyo Shimizu; Kazushi Hotta; Takashi Fukaya; Mikio Karasawa; Eiji Ikeda; Yasuyoshi Wadano (Elsevier, 2014)
Maintenance of the sporting activity of elite athletes in adapted sports can be difficult if a secondary disorder, such as a pressure ulcer, occurs. Pressure ulcers result from deep tissue injuries by external pressure. The purpose of this study was to use ultrasonography to investigate deep tissue injuries in male wheelchair basketball players of a Japanese national team, and to determine factors associated with the injuries (e.g., body mass index, class of wheelchair basketball, underlying disease, length of athletic career, and whether use of wheelchair is primarily for playing basketball). Twenty male Japanese wheelchair basketball players on the national team for the 2012 London Paralympic Games (12 representative players and eight candidate representative players) participated in this study. The sacral region and bilateral ischial regions in each athlete were examined by ultrasonography to detect low-echoic lesions indicative of deep tissue injuries. Nine (45%) players had low-echoic lesions, which were detected in 10 of 60 areas. Eight lesions were detected in the sacral region and two lesions were detected in the ischial region. More players with spinal cord injury had low-echoic lesions [9 (69.2%) of 13 players], compared to players with skeletal system disease [0 (0%) of 7 players, p = 0.002]. Players who used a wheelchair in daily life were more likely to have low-echoic lesions [8 (66.74%) of 12 players], compared to players who primarily used a wheelchair for playing basketball [1 (12.5%) of 8 players, p = 0.010]. Deep tissue injuries were detected in 45% of male Japanese wheelchair basketball players on the national team. Players with spinal cord injury and players who used a wheelchair in daily life were more likely to have deep tissue injuries, particularly in the sacral region. The lesions were small, but a periodic medical check should be performed to maintain athletes' sporting life.